PERAN ERGONOMI DALAM INDUSTRI TERHADAP KECELAKAAN KERJA BERDASARKAN MUSCULOSKELETAL DISORDERS (MSDs) - Widiastuti, Untung; Dharmosamoedero, Djati Poetryono (JURNAL GAUNG INFORMATIKA, 2015)
Along with the development of equipment technology has become a basic requirement in various jobs. This means that equipment and technology are importantsupports in an effort to increase productivity for various types of work. To improve work efficiency and productivity, the implementation of occupational safety and healthin the workplace is one form of effort to create a safe, healthy, free from environmental pollution workplaces. So that, it can reduce and or be free from work accidents andPAK which ultimately can improve efficiency and work productivity which leads to maximum profits for the company. In this case the problem that often occurs is thatworkers always do work every day whose work activities are carried out the same and repeat from day to day, so it is feared that in the long run their health will be disrupted. Musculoskeletal Disorders (MSDs) are diseases that have symptoms that attack muscles, conditions, tendons, joint ligaments, cartilage and spinal cord. FactorsCausing Complaints on Musculoskeletal Disorders: excessive muscle stretching, repetitive activity, unnatural working attitudes, secondary factors (pressure, vibration, microclimates) and combination causes (age, sex, smoking habits, physical fitness, physical strength, body size (anthropometry)). Steps to Overcome the Complaints of theMusculoskeletal System are by Engineering and Management Engineering.